Autism and Systemic Practice Special Interest Group Activities - Evans, Mairi; Thibert, Dawn; McEwen, Freda; Gordon-Jackson, Deni; Steare, David; Urbistondo Cano, Francisco; Simon, Gail (Murmurations: Journal of Transformative Systemic Practice, 2022)
This item documents the work of the Autism and Systemic Practice Special Interest Group which focuses on depathologising theory and practice with autistic people.